2019
DOI: 10.1016/j.epsl.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of channel-hillslope coupling along a tectonic gradient

Abstract: Landscape morphology reflects the spatial and temporal history of erosion. Erosion in turn embodies the competition between tectonic and climatic processes. Quantitative analysis of topography can therefore reveal the driving tectonic conditions that have influenced landscape development, when combined with theoretical understanding of erosion processes. Recent developments in the automated analysis of high-resolution (< 10 m) topographic data mean that integrated analysis of hillslope and channel topographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
(86 reference statements)
1
38
0
Order By: Relevance
“…The amount of finite deformation accommodated by these folds progressively decreases southward, such that the structure we identified could correspond to the most recently activated as an in-sequence system. Finally, while high-resolution hillslope morphology analysis has already been used to constrain rock uplift patterns in a limited number of studies (Hurst et al, 2013a(Hurst et al, , 2019Clubb et al, 2020), our results are the first to illustrate the use of such data to infer the geometry of tectonic structures at depth.…”
Section: Constraints On Tectonic Structures From Hillslope Morphologymentioning
confidence: 74%
See 4 more Smart Citations
“…The amount of finite deformation accommodated by these folds progressively decreases southward, such that the structure we identified could correspond to the most recently activated as an in-sequence system. Finally, while high-resolution hillslope morphology analysis has already been used to constrain rock uplift patterns in a limited number of studies (Hurst et al, 2013a(Hurst et al, , 2019Clubb et al, 2020), our results are the first to illustrate the use of such data to infer the geometry of tectonic structures at depth.…”
Section: Constraints On Tectonic Structures From Hillslope Morphologymentioning
confidence: 74%
“…This comparison illustrates the resolving power of high-resolution hillslope morphology analysis, which allows us to document short-wavelength patterns of erosion and uplift that are undersampled by scarcely distributed fluvial metrics. We note that Hurst et al (2019) observed a clear re- Figure 11. (a) Nondimensional erosion rate evolution from hilltop patches (mean and standard deviation binned every 1 km).…”
Section: Hillslopes and Channel Dynamicsmentioning
confidence: 89%
See 3 more Smart Citations